Diversity of Medicinal Plant Types Using Exploration Methods in Seupang Village, Koper Village, Tangerang Regency - Rizqiyah, Dedeh; Muzdalipah, Elip; Sidik, Permana; Azaziyah, Azaziyah; Pranitha, Yuyun (Jurnal Biologi Tropis, 2025)
It is necessary to cultivate medicinal plants in the yard because medicinal plants can be used as alternative medicine. The purpose of this study was to determine the function and types of plants that can be used as medicine. The research method was carried out by exploration which included tracking, exploring, searching for and collecting all types of medicinal plants. The results of the study found various types of plants that have the potential to be used as medicine including; bidara, telang, moringa oleifera, red binahong, taro, papaya leaves, mulberry, celery, cat's whiskers, ciplukan, broken glass, galangal leaves, avocado leaves, and betel leaves. These plants are widely found around the yards of residents of Koper Village, Seupang Village, Tangerang Regency. On average, plants that have a function as medicine contain active substances such as flavonoids, saponins, alkaloids, and polyphenols which act as antioxidants, anti-inflammatories, antiseptics and so on. This study provides a lot of important information about the existence of medicinal plants in Seupang Village, can increase awareness for the community as an effort to preserve medicinal plants that were previously not noticed.